Indications of amputation after limb-salvage surgery of patients with extremity-located bone and soft-tissue sarcomas: A retrospective clinical study - EROL, BÜLENT; ŞİRİN, EVRİM (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2021)
Objective: This study aimed to investigate amputation-related factors after limb-salvage surgery (LSS) in patients with extremity-located bone and soft-tissue sarcomas and determine the relationship between these factors and patient survival. Methods: In this retrospective study at our institution, patients in whom LSS was first performed because of an extremity-located musculoskeletal sarcoma, and subsequently amputation was carried out for various indications were included. Patient and tumor characteristics, details of surgical procedures, indications of amputation, number of operations, presence of metastasis before amputation, and post-amputation patient survival rates were analyzed. Results: A total of 25 patients (10 men, 15 women; mean age=41.96 +/- 21.88 years), in whom amputation was performed after LSS as initial resection of an extremity sarcoma or re-resection(s) of a local recurrence, were included in the study. The leading oncological indication for amputation was local recurrence that occurred in 18 (72%) patients. Non-oncological indications included prosthetic infection in 5 (20%), mechanical failure in 1 (4%), and skin necrosis in 1 (4%) patient. The patients underwent a median of 2 (range, 1-4) limb-salvage procedures before amputation. Distant organ metastasis was detected in 22 (88%) patients during follow-up; in 13 (52%) of these patients, metastasis was present before amputation. A total of 11 (44%) patients were alive at the time of study with no evidence of the disease (n=3) or with disease (n=8), and 14 (56%) patients died of disease. The mean overall and post-amputation survival were 47 +/- 20.519 (range, 11-204) months and 22 +/- 4.303 (range, 2-78) months, respectively. The median follow-up was 27 (range, 6-125) months. Conclusion: The most common causes of amputation after LSS were local recurrence and prosthetic infection. Patients who underwent amputation after LSS developed a high rate of distant organ metastasis during follow-up and had reduced survival.
Keywords: Extremity; Sarcoma; Amputation; Limb salvage surgery; Local recurrence; SURGICAL-MANAGEMENT; RISK